The digital economy, privacy, and CBDC - Toni Ahnert; Peter Hoffmann; Cyril Monnet (European Central Bank (ECB), 2022)
We study a model of financial intermediation, payment choice, and privacy in the digital economy. Cash preserves anonymity but cannot be used for more efficient online transactions. By contrast, bank deposits can be used online but do not preserve anonymity. Banks use the information contained in deposit flows to extract rents from merchants in need of financing. Payment tokens issued by digital platforms allow merchants to hide from banks but enable platforms to stifle competition. An independent digital payment instrument (a CBDC) that allows agents to share their payment data with selected parties can overcome all frictions and achieves the efficient allocation.
Keywords: D82; E42; E58; G21; 330; Central Bank Digital Currency; Privacy; Payments; Digital Platforms; Financial Intermediation